Pharmacological treatment of actinic keratosis - Ewa Zwierzyńska; Anna Zawistowska; Bogusława Pietrzak (Termedia Publishing House, 2016)
Actinic keratosis (AK) is a disease characterized by hyperkeratotic lesions on skin damaged by ultraviolet. radiation. These lesions may progress to squamous cell or basal cell carcinoma. Currently pharmacotherapy and different surgical procedures are used in AK therapy. The most common treatment options are 5-fluorouracil, imiquimod, diclofenac, ingenol mebutate, and first and third generation retinoids (retinol, adapalene, tazarotene). Furthermore, research is being carried out in order to test new medications including nicotinamide, resiquimod, piroxicam, potassium dobesilate and oleogel based on a triterpene extract (betulin, betulinic acid). Recently, the preventive effect of acetylsalicylic acid and celecoxib has also been investigated.